2001
DOI: 10.1007/bf03172995
|View full text |Cite
|
Sign up to set email alerts
|

Learning from expository texts: Effects of the interaction of prior knowledge and text structure on responses to different question types

Abstract: The objective of this study was to verify the effects of the interaction between text structures and prior knowledge on memory and learning from expository texts. It examined the effects of two levels ofprior knowledge and two types of mixed structures on a post-reading questionnaire. A total of 119 French-speaking, sixth-grade subjects were selected on the basis of a multiple-choice questionnaire. This questionnaire served to distinguish two groups, one possessing a high level ofprior knowledge about the topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
1
9
0
4
Order By: Relevance
“…The absence of correlation between visual working memory and accuracy of reading was also found in previous studies (Amand, 2001;Budd, Whitney & Turley, 1995;Sadatnia & Ketabi, 2016). This could be attributed to the fact that working memory does not play a role in superficial comprehension tests.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The absence of correlation between visual working memory and accuracy of reading was also found in previous studies (Amand, 2001;Budd, Whitney & Turley, 1995;Sadatnia & Ketabi, 2016). This could be attributed to the fact that working memory does not play a role in superficial comprehension tests.…”
Section: Discussionsupporting
confidence: 77%
“…The passages were expository descriptive texts. These texts were chosen because previous research has concluded that expository descriptive texts represent the simplest model of texts (Amand, 2001;Sadatnia & Ketabi, 2016). The passages covered four different topics: (1) history of arts, (2) health, (3) history of science, and (4) energy.…”
Section: Reading Test Materialsmentioning
confidence: 99%
“…Prior knowledge is considered to be an essential component of text comprehension (Armand, 2001;Pressley, 2000;Voss, Vesonder & Spilich, 1980). The implication of such a view is that to build a mental representation of what the text is about, the situation model (Kintsch, 1988(Kintsch, , 1998, the reader needs to combine textual information with his/her generic units of world knowledge (e.g., schemas) and other sources of knowledge, such as personal knowledge and experiences, knowledge about language, and knowledge about the specific communicative situation (McNamara & Kintsch, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Socioconstructivist research on reading comprehension argues that this process derives from the interaction between the reader and the text (Armand, 2001;Best et al, 2005). This step supports such an interaction as it helps the reader to focus on the text characteristics and in particular on its advance organizers (Ausubel, 1960;Boscolo, 1997).…”
Section: Prior Knowledge Activationmentioning
confidence: 96%